Clinical study. Statistical data - Gateño Yaffe, Nisso (Cirugía del Uruguay, 1973)
Our work is based on the analysis of 100 clinical histories of soft tissue sarcomas with the limitations that arise from histopathological classification and topography. to adjust to the subject within the limits set by the Coordinator of the Table.